Nature Exploration in the Schoolyard: Creating a Play Environment that Teaches Environmental Care to Young Children - Sriyanto, Agus; Fa'izah, Tuhrotul; Entriza, Aditya Niko; Saputra, Alan Lutfi Gesang (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Early environmental education is important for developing an environmentally conscious character. This study aims to describe the implementation of nature exploration in the schoolyard in developing environmental awareness in early childhood at RA Nawa Kartika VIII Sidolaju Widodaren Ngawi. Using a qualitative approach with a case study design, data were collected through observation, interviews, and documentation. The results of this study found that nature exploration activities in the schoolyard can increase environmental awareness and develop children's cognitive, socio-emotional, and motor skills. Direct involvement in activities such as planting, cleaning the environment, and making compost fosters a sense of responsibility from an early age. Obstacles faced can be overcome through collaboration and training. This study recommends optimal use of the schoolyard as an environment-based learning medium.